Simulation And Analysis Detection Of Pulpitis Via Radiograph Periapical Using Dct, Wavelet, And Curvelet Transform And Lvq Classification - Tengku Ahmad Wira Giovany; Bambang Hidayat; Suhardjo Sitam (eProceedings of Engineering, 2015)
ABSTRACT lately the development of technology allow us to do human work easily. for example in medical area, lots of doctor has already use technology as their tools in order to cure or to diagnose disease. Biomedical engineering is the application of engineering principles and design concepts to medicine and biology for healthcare purposes. Pulpitis as one of the disease that can't be detected with normal eyes ,in order to make decision of this disease doctor need a lots of information including Periapical Radiograph Image and Historical review from patient. after getting those information doctor try to diagnose wheter this patient get pulpitis or healthy,but its not easy to made decision just based on those two things. Based on the problem above, the author makesâ€Simulation and Analysis of Pulpitis Via Periapical Using DCT,Wavelet,And Curvelet Transformâ€, which is an application that can allow doctors caught pulpitis of a periapical radiograph Keyword : Periapical Radiograph, DCT , Wavelet ,Curvelet , LVQ , Pulpitis